Preferensi, Persepsi, dan Harapan Pengguna Terhadap Rumah Sakit Ibu dan Anak (RSIA) - Intan Reyndan Fananti; Annisa Safira Riska; Hanson Endra Kusuma (EMARA: Indonesian Journal of Architecture, 2021)
The hospital building is designed to fulfill and accommodate every user's needs, namely patient and general users/visitors. The users discussed in this research are patients and general users. This research aims to determine preferences (reasons for choosing), perceptions (strengths and weaknesses), and user’s expectations (patients and general users) of Mother & Child Hospital. The research was conducted qualitatively using a grounded theory approach. Data were collected using an online questionnaire containing open-ended main questions and distributed freely (non-random sampling). The collected data analyzed qualitatively using the content analysis (open coding) method. The result show Mother & Children Hospital’s patient and general user’s differences in preferences, perception, and expectations on visual architectural aspects, non-visual architectural aspects, and non-architectural aspects. The preferences, perceptions, and expectations of patients and general users tend to be non-architectural in terms of their preferences. There is only one difference, it's in the general user's perception of the Mother & Children Hospital's weakness, where the perception lies in the visual architectural aspect. The tendency for patients and general users are found in the category of service, facilities, quality of medical personnel, location, and parking.